Pemidanaan Terhadap Tindak Pidana Penipuan (Studi Putusan No. 1096/Pid.Sus/2020/PN Jkt.Brt): Criminalization of the Crime of Fraud (Study Decision Number 1096/Pid.Sus/2020/PN Jkt.Brt) - Adinda Putri Elin; Ermania Widjajanti (Faculty of Law, Universitas Trisakti, 2024)
Based on the Public Agency for Statistics, during Covid 19, Crime in Indonesia increased, the highest number of crimes in Metro Jaya was 5,115 incidents. One of them is in Decision No. 1096/Pidsus/PN Jkt.Brt, the judge charged the defendant with Article 372 of the Criminal Code on Embezzlement, but the elements were not fulfilled. The formulation of the problem of this article is how the suitability of the Sanctions imposed by the Judge's Decision is appropriate in (Study of Decision No. 1096/pid.sus/2020/PN Jkt.Brt) and how the suitability of Criminal Sanctions on the Perpetrator of the Crime of Fraud is in accordance with the objectives of punishment (Study of Decision No. 1096/Pid.sus/2020/PN Jkt.Brt). This research method uses normative juridical research which is descriptive analytical in nature, using secondary data obtained through literature studies and processed qualitatively and then drawing conclusions in a deductive manner. The results of the discussion of the defendant did not fulfill the elements of Article 372 of the Criminal Code and the punishment used retributive theory. The conclusion is that there is a discrepancy with the punishment imposed by the judge and the imposition of criminal sanctions is in accordance with the purpose of punishment.